(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
Primulina wenii (Gesneriaceae) is described and illustrated here as a new species. Morphologically, this new species resembles P. juliae (Hance) Mich. Möller & A. Weber, but it is distinct from the latter by some obvious features in leaf blade, bract, indumentum, corolla, filament, stigma and pistil. Nuclear ribosomal internal transcribed spacer (ITS) region and plastid trnL-F intronspacer (trnL-F) DNA sequence data from the new species and its 22 relatives are used to determine the systematic position of the new species within Primulina. Molecular evidence suggests that P. wenii is strongly supported as a sister to a clade in which P. juliae is included. The conservation status of P. wenii is assessed as "Critically Endangered" (CR) according to IUCN Red List categories and criteria. Bangladesh J. Plant Taxon. 24(2): 173–182.